Trastuzumab emtansine in locally advanced or metastatic HER2 positive breast cancer; GENESIS-SEFH drug evaluation report - Patricia Miranda Romero; Roberto Marín Gil (Farmacia Hospitalaria)
Trastuzumab emtansina (T-DM1) is an antibody-drug conjugate directed against the HER2 for the treatment of HER2+ mestastatic breast cancer (MBC), who has previously received trastuzumab plus a taxane. According to the results of the EMILIA trial versus lapatinib plus capecitabine T-DM1 shows an improvement in progression-free survival (PFS) and the overall survival (OS). It has a favorable profile reducing the incidence of grade 3-4 adverse reactions such as hand-foot syndrome and diarrhea. On the contrary increases significantly severe thrombocytopenia; bleeding risk and liver function should also be monitored. With the current import price T-DM1 has a cost per QALY of over 120,000 €. The price of the drug for the Spanish NHS has not yet been established. Drug cost would be the key factor in the sensitivity analysis and a 50% reduction in the price of the drug would place it close to the threshold of cost-effectiveness usually considered in our midst. According to the budget impact model used, a maximum of 1,218 patients / year and the budgetary impact throughout the Spanish state would be at € 70,490,850. In the initial analysis no advantage was found for T-DM1 in those patients without visceral involvement. Although a subsequent re-analysis of the results of PFS in which the definition of visceral involvement was specified a significant benefit was shown in this subgroup. We believe that this approach introduces a high degree of uncertainty, which does not guarantee the benefit achieved for this subgroup of patients